Coupling of abiotic stresses and phytohormones for the production of lipids and high-value by-products by microalgae: A review. (February 2019) - Zhao, Yongteng; Wang, Hui-Ping; Han, Benyong; Yu, Xuya
Graphical abstract: Highlights: The effect of abiotic stress on metabolite enhancement in microalgae was reviewed. The coupling of hormone and abiotic stress are vital for metabolite production in microalgae. Mechanisms underlying phytohormone-mediated lipid biosynthesis were analysed. Abstract: Microalgae can produce lipids and high-value by-products under abiotic stress conditions, including nutrient starvation, high light intensity, extreme temperature, high salinity and the presence of heavy metals. However, the growth and development of microalgae and the accumulation of metabolites may be inhibited by adverse stresses. In recent years, phytohormones have emerged as a topic of intense focus in microalgae research. Phytohormones could sustain the growth of microalgae under abiotic stress conditions. In addition, the combination of plant hormones and abiotic stresses could further promote the biosynthesis of metabolites and improve the ability of microalgae to tolerate abiotic stresses. This review primarily focuses on the regulatory effects of exogenous phytohormones on the biosynthesis of metabolites by microalgae under adverse environmental conditions and discusses the mechanisms of phytohormone-mediated cell growth, stress tolerance and lipid biosynthesis in microalgae under abiotic stress conditions.